On vicious worlds - Jacobs, Bethany (Novelist) (Jacobs, Bethany (Novelist). Kindom trilogy, 2024)
"The Jeveni have finally found freedom on the distant planet Capamame, delivered from Kindom oppression through their alliance with stoic Cleric Chono, intrepid caster Jun Ironway, and Six, the wildly unpredictable manipulator who has outwitted the Nightfoot family. But when Six and Chono return to the Treble star systems, the dream of freedom meets a dangerous test. The Secretaries of the Kindom are intent on reclaiming power in the Treble, as well as control over the Jeveni. Meanwhile, Jun Ironway and Jeveni collector Masar Hawks struggle to protect Capamame from a population brimming with resentment, not to mention a faceless saboteur spreading mayhem and murder. As the two groups struggle to outwit their enemies, divergent battles wend toward a climatic reunion that will spark a revolution. But over it all hangs the cruel legacy of Esek Nightfoot, whose rippling effects may prove impossible to survive"--